How employee empowerment really works in Chinese private-owned companies? Insights from Jin Fong Group Ltd, China - Zeng, Dandan (2008)
Today's business market is increasingly competitive in China. Many private-owned companies have confronted conflicts in order to make better business. Respond to such pressures, more and more Chinese private firms are implementing western empowerment concepts into management for increasing internal efficiency. However, China is a high power distance country that minor decisions are taken by top management group rather than passed down the organizational hierarchy. Moreover, the Confucian value may become the obstacle for authority delegating in Chinese private-owned firms.